The Utilization of Selected Maranao Arts and Practices in Teaching Ratio and Proportion, Triangle Similarities and Circles - A. Aniñon, Annie; A. Sombilon, Virginia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study is an emergent, exploratory, qualitative research. Ethnographic concepts were used to guide the work of the researcher in teaching geometry for one grading period. Mathematical concepts imbedded in some Maranao arts and practices were integrated in the teaching of some geometric concepts. A teacher-demonstrator conducted the class while the researcher acted as a participant-observer, recording daily observations in her field notes. A questionnaire was administered and interviews were conducted to 32 third year Maranao students of Baloi National High School who were the subjects of the study. Interviews were also conducted with three Maranao families whose responses were utilized in the development of the lesson plans in the "culture-integrated" math class. Pre and post tests on Achievement and mathematics Attitude Inventory were also administered. The students were made to write journals where they could express their feelings towards the integration of their culture in the lessons. Data obtained from responses to the questionnaire, interviews and journals were analyzed phenomenographically and by the triangulation method. Results of the study showed that the integration of selected Maranao arts and practices in the math lessons helped facilitate students' understanding. The feeling of "belongingness" was observed throughout the duration of the investigation. Treating them and their culture as important people made them proud and happy of being Maranaos. Students realized that it is possible to relate their culture to mathematics and learned more about their culture in the process. Attitude of the students towards mathematics, however. was not affected by the integration of Maranao culture in the math lessons.